N-Formylation of Anilines with Silica Sulfuric Acid under Solvent-Free Conditions. (22nd November 2012) - Habibi, Davood; Rahmani, Payam; Akbaripanah, Ziba
Abstract : N -formylation of primary and secondary amines was carried out with formic acid in the presence of silica sulfuric acid under solvent-free conditions to give the corresponding formamides in excellent yield and short reaction times.